Left ventricular structure and function – Associations with cardiovascular risk factors from childhood to adulthood. The Cardiovascular Risk in the Young Finns Study - Heiskanen, Jarkko (fi=Turun yliopisto|en=University of Turku|, 2022)
Background: Despite improvements in the treatment of cardiovascular diseases, heart failure remains a challenge that causes considerable morbidity and mortality in aging populations. Left ventricular (LV) remodeling and changes in LV diastolic function, which precede heart failure, are suggested to stem from lifestyle factors during the whole life course. However, the determinants of LV remodeling and diastolic function in healthy populations are inadequately known. Aims: The first aim was to examine the associations between cardiovascular risk factors and LV diastolic function in adulthood. The second aim was to examine the effects of early-life adiposity and systolic blood pressure on LV mass and remodeling. The third aim was to investigate whether early life exposure to cardiovascular risk factors is associated with LV diastolic function in adulthood. Materials and Methods: This thesis uses data from the Cardiovascular Risk in Young Finns Study, a population-based follow-up study that recruited n=3596 participants aged 3 to 18 in 1980. Cardiovascular risk factors have been measured repeatedly in follow-up visits between the years 1980-2011. In 2011, a follow-up with cardiac ultrasound was performed on n=1994 participants aged 34-49 years. Acquired data were analyzed using standard statistical methods. Results: In adulthood, the determinants for LV diastolic function included systolic blood pressure, waist circumference, alanine aminotransferase, smoking, shorter stature, and female sex. Exposure to high body mass index in early life was associated with higher adulthood LV mass and risk for eccentric hypertrophy independently of adult obesity status. Early life risk factors for lower LV diastolic function in adulthood included the cumulative burden of higher adiposity and lower levels of physical activity. Conclusions: The longitudinal burden of cardiovascular risk factors is associated independently with changes in LV diastolic function and LV remodeling. If these associations turn out to be causal, these results can be applied to guiding the primordial prevention and targeting the early interventions for individuals with increased cardiovascular risk factor burden.

Kardiovaskulaaririskitekijät lapsuudesta aikuisuuteen - Yhteydet sydämen vasemman kammion toimintaan ja rakenteeseen Tausta: Sydämen vajaatoiminta lisää merkittävästi iäkkäiden sairastavuutta ja kuolleisuutta. Tutkimuksissa on havaittu, että sydämen vajaatoimintaa voi edeltää vasemman kammion muovautuminen -ja diastolisen toiminnan muutokset. Niiden arvioidaan johtuvan elintapojen aiheuttamasta pitkäkestoisesta altisteesta. Ei ole kuitenkaan selvää, mitkä ovat itsenäisiä riskitekijöitä sydämen muovautumiseen ja vasemman kammion diastolisen toiminnan muutoksiin terveessä väestössä. Tavoite: Tutkimuksen tavoitteena oli tutkia vasemman kammion diastolisen funktion ja kardiovaskulaaririskitekijöiden välisiä yhteyksiä aikuisuudessa. Tavoitteena oli myös tutkia lapsuuden ja nuoruuden kardiovaskulaaririskitekijöiden altisteen yhteyttä vasemman kammion diastoliseen toimintaan aikuisuudessa sekä lapsuuden ja nuoruuden systolisen verenpaineen ja kehonkoostumuksen yhteyttä vasemman kammion massaan ja muovautumiseen aikuisuudessa. Materiaalit ja menetelmät: Tämä väitöskirja on osa Lasten Sepelvaltimotaudin Riskitekijät -seurantatutkimusta. Seuranta alkoi vuonna 1980, jolloin tutkimuspopulaatio koostui n=3596 3–18-vuotiaasta lapsesta ja nuoresta. Kardiovaskulaaririskitekijöitä mitattiin säännöllisesti seurantakäynneillä ja vuonna 2011 seurantakäynnillä tehtiin sydämen ultraäänitutkimus n=1994 34–49-vuotiaille tutkittaville. Data on analysoitu standardoiduilla tilastomenetelmillä. Tulokset: Aikuisuudessa vasemman kammion diastolisen funktioon muutoksiin yhdistettiin systolinen verenpaine, vyötärönympärys, alaniiniaminotransferaasi-entsyymi, tupakointi, pituus ja sukupuoli. Lapsuuden riskitekijät matalammalle vasemman kammion diastoliselle funktiolle olivat rasvaisempi kehonkoostumus ja vähäisempi liikunnan määrä. Lisäksi korkeampi painoindeksi lapsuudessa ja nuoruudessa oli yhteydessä korkeampaan vasemman kammion massaan ja eksentrisen hypertrofian riskiin riippumatta painoindeksistä aikuisuudessa Johtopäätökset: Pitkäaikainen kardiovaskulaaririskitekijöiden altiste on yhteydessä vasemman kammion diastoliseen toimintaan ja vasemman kammion muovautumiseen. Jos taustalla on syy-seuraussuhde, voidaan tuloksia hyödyntää ennaltaehkäisyssä ja elintapamuutosten kohdistamisessa.